Light‐induced modifications of the outer retinal hyperreflective layers on spectral‐domain optical coherence tomography in humans: an experimental study. Issue 7 (4th January 2021) - Mathis, Thibaud; Vasseur, Vivien; Zuber, Kevin; Arej, Nicolas; Loria, Olivier; Kodjikian, Laurent; Sennlaub, Florian; Mauget‐Faÿsse, Martine
Abstract: Purpose: Numerous small hyperreflective dots (HRDs) can be seen within the hyporeflective layer between the ellipsoid zone (EZ) and the interdigitation zone (IZ) on C‐scan spectral‐domain optical coherence tomography (SD‐OCT) with a yet unknown variation under light conditions. The aim of this study was to explore light‐induced SD‐OCT changes in these HRDs. Methods: The study subjects were randomly assigned to two groups: Group 1 experienced a dark adaptation protocol followed by intense retinal photobleaching, while Group 2, serving as the control group, was exposed to constant ambient light without any variation. The number of HRDs was automatically counted. Results: Twenty healthy volunteers were prospectively included. The number of HRDs differed significantly over time (p = 0.0013). They decreased in Group 1 after dark adaptation and retinal photobleaching before returning to baseline levels 30 min later; conversely, they remained relatively constant in Group 2 throughout the study (p < 0.001). Light‐skinned subjects had less HRD than dark‐skinned subjects. Conclusion: We observed light‐induced modifications in the space between the EZ and the IZ. We hypothesize that the HRDs visible in this zone correspond to melanosomes that are mobilized during the light stimulation protocol. Larger studies are recommended to further evaluate and confirm light‐induced SD‐OCT changes under physiological and pathological conditions.